2021
DOI: 10.21037/jgo-20-368
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dual-energy spectral computed tomography-based nomogram for the preoperative discrimination of histological grade in colorectal adenocarcinoma patients

Abstract: Background: The usefulness of a dual-energy spectral computed tomography (DESCT)-based nomogram in discriminating between histological grades of colorectal adenocarcinoma (CRAC) is unclear. This study aimed to develop such a nomogram and assess its ability to preoperatively discriminate between histological grades in CRAC patients. Methods: Primary tumors monochromatic CT value, iodine concentration (IC) value, and effective atomic number (Eff-Z) in the arterial (AP) and venous phases (VP) were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
(31 reference statements)
4
3
0
Order By: Relevance
“…Advanced-stage or high-grade CRAC presents increased angiogenesis and abnormal microvascular permeability, leading to higher NIC values. Our results agreed with those of Cao et al and Gong et al, who used rapid kV switching dual-energy CT (Discovery 750 HD, GE) to evaluate the colon cancer differentiation degree (44,45). They showed that the IC and NIC of high-grade colon cancer were significantly higher than that of low-grade colon cancer; Therefore, quantitative parameters of iodine concentration can provide helpful information in distinguishing low-from high-grade colorectal cancer.…”
Section: B Asupporting
confidence: 92%
“…Advanced-stage or high-grade CRAC presents increased angiogenesis and abnormal microvascular permeability, leading to higher NIC values. Our results agreed with those of Cao et al and Gong et al, who used rapid kV switching dual-energy CT (Discovery 750 HD, GE) to evaluate the colon cancer differentiation degree (44,45). They showed that the IC and NIC of high-grade colon cancer were significantly higher than that of low-grade colon cancer; Therefore, quantitative parameters of iodine concentration can provide helpful information in distinguishing low-from high-grade colorectal cancer.…”
Section: B Asupporting
confidence: 92%
“…The lower the degree of differentiation means the faster the proliferation of tumor cells, the relatively insu cient blood supply of the tumor, more obvious tumor heterogeneity, more necrosis which all cause a decrease in quantitative parameters of SDCT. Our results were consistent of the past studies [7,12,13].…”
Section: Discussionsupporting
confidence: 94%
“…Colorectal adenocarcinoma (CRAC) is the most common histological type of colorectal cancer [11]. Up to date, there has been a few studies [7,[12][13][14] that reported the application of SDCT imaging in predicting the pathological staging and histological grading of CRAC, the results from these previous studies are not consistent [15][16][17][18] and need more research to con rm. Therefore, the purpose of this study is to explore the diagnostic value of CRAC differentiation grade, T stage, and lymph node metastasis stage based on different spectral parameters, in order to provide new ideas for clinical treatment and prognosis of CRAC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This statement correlates with what was found in our study, where a low histological grade was associated with better survival outcomes among the CRC patients investigated. Existing evidence indicates that low-grade tumors exhibit less aggressive and invasive behavior than high-grade tumors and improved survival outcomes [ 22 , 25 , 26 , 27 , 28 , 29 , 30 ]. However, it is important to mention that other factors, such as tumor stage, patient age, and general health status, have also been recognized as factors that may influence disease prognosis [ 23 , 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%